Case report: Transplantation of human induced pluripotent stem cell-derived cardiomyocyte patches for ischemic cardiomyopathy - Miyagawa, Shigeru; Kainuma, Satoshi; Kawamura, Takuji; Suzuki, Kota; Ito, Yoshito; Iseoka, Hiroko; Ito, Emiko; Takeda, Maki; Sasai, Masao; Mochizuki-Oda, Noriko; Shimamoto, Tomomi; Nitta, Yukako; et al. (Frontiers in Cardiovascular Medicine, 2022)
Despite major therapeutic advances, heart failure, as a non-communicable disease, remains a life-threatening disorder, with 26 million patients worldwide, causing more deaths than cancer. Therefore, novel strategies for the treatment of heart failure continue to be an important clinical need. Based on preclinical studies, allogenic human induced pluripotent stem cell-derived cardiomyocyte (hiPSC-CM) patches have been proposed as a potential therapeutic candidate for heart failure. We report the implantation of allogeneic hiPSC-CM patches in a patient with ischemic cardiomyopathy (ClinicalTrials.gov, #jRCT2053190081). The patches were produced under clinical-grade conditions and displayed cardiogenic phenotypes and safety in vivo (severe immunodeficient mice) without any genetic mutations in cancer-related genes. The patches were then implanted via thoracotomy into the left ventricle epicardium of the patient under immunosuppressive agents. Positron emission tomography and computed tomography confirmed the potential efficacy and did not detect tumorigenesis in either the heart or other organs. The clinical symptoms improved 6 months after surgery, without any major adverse events, suggesting that the patches were well-tolerated. Furthermore, changes in the wall motion in the transplanted site were recovered, suggesting a favorable prognosis and the potential tolerance to exercise. This study is the first report of a successful transplant of hiPSC-CMs for severe ischemic cardiomyopathy.